Critical Evaluation of Refinish Paint Industry in the Automobile Sector: With Special Reference to City of Jaipur, Rajasthan - Kumar Chaudhary, Kuldeep; Madhukar, Vikas (International Journal of Psychosocial Rehabilitation, 2020)
The main reason for this growth can be linked to the increasing number of vehicles on the roads and on the other hand the automobile industry is one such industry that is one of the apex consumers of industrial paints. Till the last few years of 20th century nitrocellulose based paints are used in the automotive market and then came the Polyurethane based paints that has changed the face of the market. This present study evaluates the scenario of refinish paint industry. The researcher had considered the primary data for the analysis purpose and the data is being presented graphically. SPSS ver. 23.0 is used to analyze the data.